Autonomous architecture in Flanders : the early works of Marie-Jose van Hee, Christian Kieckens, Marc Dubois, Paul Robbrecht and Hilde Daem. - Voet, Caroline; Vandermarliere, Katrien; De Caigny, Sofie; Schrijver, Lara (Leuven : Leuven University Press, 2016)
Five well-known graduates of the class of 1974 of the St Lucas Institute in Ghent, Marie-José Van Hee, Paul Robbrecht & Hilde Daem, Christian Kieckens and Marc Dubois can be considered as leading architects of their generation. To the present-day, their professional careers and legacy have been of great importance to the development of Flemish architecture. In their early works and writings, they established a distinct architectural language, rooted in historical knowledge and with a reflection to art and craftsmanship. Architecture was singled out as a spatial phenomenon with an autonomous logic grounded in inhabitation and experience. This generation represents a significant turn towards architectural autonomy in Flanders which resonated with similar international developments in the late 1970s. Moreover they played a decisive role in the emancipation and professionalization of the architectural culture in Flanders. Exhibition: De Singel, Antwerp, Belgium (12.02-05.06.2016).
boek